Antes de perder la memoria: testimonio, amistad y epistolario (Altre Modernità, 2021)
This paper analyzes the book Antes de perder la memoria (2015), co-authored by Ana María Jiménez and Teresa Izquierdo. Both women were militants of Movimiento de Izquierda Revolucionaria (MIR) and experienced clandestinity, political imprisonment in Villa Grimaldi and Tres Álamos, the loss of comrades and friends, exile in France, and the subsequent return to Chile. The book relates all these milestones in the authors' lives and presents their testimonies in a new way, since it is written as an epistolary exchange between two friends, which emphasizes the shared experience and their point of view as militant women. Throughout the commemoration of 40 years of friendship and political commitment, Ana María and Teresa build a retrospective look that contains a strong gender perspective. In this article I will explore the following three issues: the epistolary nature of the testimony; the idea of friendship as a mode of affective exchange and reception, and the broad temporal framework of the text, which narrates the experience of fear during the 80s.
Keywords: testimony; correspondence; friendship; militancy